Dans l’excès de visibilité : jeu du montrer / cacher dans les photographies de Lorna Simpson - Claudine Armand (Sillages Critiques)
In Lorna Simpson’s complex and multifaceted work, words and images are often set side by side and they collide with each other. A double tension is at work which emerges on the one hand, from the interaction of the verbal and the iconographic and on the other hand, from the choice and handling of the subject. Most often, the photographs of this African-American artist represent a human figure, an object or an outdoor/indoor scene which clearly stand out against a neutral backdrop. However, the bodies are often dislocated and the spaces are fragmented. Linguistic signs are sometimes visible around the composition or they cover it partially, thereby blurring the meaning of the picture. The rigorously constructed photographs along with the serial mode in which they operate are exposed/overexposed to the viewer’s gaze and have an unsettling presence. The object of this paper is to analyze the various compositional devices and strategies used by the artist in her ambiguous work that oscillates constantly between showing and hiding.